Analisis SWOT Konversi Koperasi Konvensional ke Koperasi Syariah di Koperasi Wanita Syariah Cilinaya Indah - Galuh Ratna Mutia (Jurnal Ekonomi dan Bisnis Indonesia, 2022)
The main problem in this research is how to implement the convertion of conventional cooperatives to sharia cooperatives in Koperasi Wanita Syariah Cilinaya Indah. The purpose of this study was to conduct a SWOT analysis in the implementation of the conversion of conventional cooperatives to sharia cooperatives in Koperasi Wanita Syariah Cilinaya Indah. The type of research that the author does is field research with a qualitative approach, namely exploring the phenomena interpretively related to the strengths, weaknesses, opportunities and threats challenges of the the convertion of conventional cooperatives to sharia cooperatives in Koperasi Wanita Syariah Cilinaya Indah. The results show that (1) Koperasi Wanita Syariah Cilinaya Indah expand expand their activities as consumer cooprative (2) increase the number of members by recruting new members who are colleagues of cooperative members (3) conduct eduacation and training on the topic of sharia cooperatif and conduct workshop about the benefits and advantages of participating in cooperative activities (4) utilization of developments in information and communication technology can make it easier for administrators to carry out cooperatuive activities